Psychological recreation of overcoming failures and achieving success by young rhythmic gymnasts aged 6-8 - Julia Golenkova; Tatyana Kravchuk; Nina Sanzharova; Vladimir Potop; Karina Filon (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Performing physical exercises in rhythmic gymnastics requires not only physical ability, but also psychological stability and a suitable recreational environment. The satisfaction of doing gymnastic exercises is an important component of children's success. The aim of this study: to investigate the impact of psychological means of motivation and recreation, including intrinsic and extrinsic factors, on the performance and success of young gymnasts aged 6-8 in rhythmic gymnastics exercises.